2018
DOI: 10.1016/j.aninu.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Thyme oil inclusion levels in a rabbit ration: Evaluation of productive performance, carcass criteria and meat quality under hot environmental conditions

Abstract: The aim of this study was to determine the impact of thyme essential oil supplementation in rabbit rations on performance, carcass criteria, and meat quality under hot environmental conditions. A total of 75, 4-week-old Californian male rabbits were assigned to 5 dietary treatments until 12 weeks of age. The rabbits were reared in an open house system (38 °C average ambient temperature and 26% to 35% relative humidity). Treatments were as follows: unsupplemented standard ration, negative control (CON); standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 27 publications
8
33
0
Order By: Relevance
“…In current study, the main active component of TEO was thymol which constitutes 40% relative of its analysed composition. The composition of TEO used in the present study was consistent with those reported in the literature [ 2,10]. The current study showed that BW gain and FCR were improved in rabbits fed a control diet supplemented with TEO up to 180 mg/kg compared to PC and NC groups.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In current study, the main active component of TEO was thymol which constitutes 40% relative of its analysed composition. The composition of TEO used in the present study was consistent with those reported in the literature [ 2,10]. The current study showed that BW gain and FCR were improved in rabbits fed a control diet supplemented with TEO up to 180 mg/kg compared to PC and NC groups.…”
Section: Discussionsupporting
confidence: 89%
“…These improvements may be due to the active compounds stimulated digestive enzymes and therefore leads to improve nutrient digestibility [ 6,23]. Similar results were reported supplementation of TEO with olive oil improved growth performance of male Californian rabbits under high temperature environments [ 2]. Likewise, oral administration of aqueous thyme extract with 50 mg/kg BW improved (P < 0.001) BWG, feed intake and FCR of rabbits compared to control [ 24].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results are in concordance with Abou‐elkhair et al () who showed a significant effect of thyme on weight gain and feed conversion, also, recorded its effect on stimulation of appetite and feed intake. Abdel‐Wareth, Taha, Südekum, and Lohakare () who reported that supplemented thyme oil to diet up to 150 mg/kg improved feed consumption and growth rate of rabbits. However, these results are in disagree with Dalle‐Zotte, Sartori, Bohatir, Remignon, and Ricci () who reported a non‐significant effect of thyme on weight gain and FCR.…”
Section: Discussionmentioning
confidence: 99%